DOI: 10.11606/d.3.2006.tde-31032008-101929
|View full text |Cite
|
Sign up to set email alerts
|

Estudo do comportamento do coeficiente de desgaste e dos modos de desgaste abrasivo em ensaios de desgaste micro-abrasivo.

Abstract: Aos Professores da "Escola Estadual Prof a Pedra de Carvalho", pela formação do 1 o. e 2 o. grau e incentivo na continuação dos estudos. Aos Professores das escolas SENAI Almirante Tamandaré e SENAI Mario Amato, pela amizade, formação profissional, incentivo na continuação dos estudos e rigor na disciplina. Aos Professores da Faculdade de Engenharia Industrial, pela formação e incentivo ao início da Pós-Graduação. Ao Professor Roberto Martins de Souza, pessoa de fundamental importância ao longo deste caminho, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0
19

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 9 publications
1
5
0
19
Order By: Relevance
“…The effect of oxidative wear in the test under the 8.3-N load in this study could be confirmed by constructing curves of the wear rate under the contact load to illustrate the wear transition that has been described by Cozza [12]. Further tests under different loads should be performed in a future study for this purpose.…”
Section: Wear Tests On the Base Materialssupporting
confidence: 66%
See 1 more Smart Citation
“…The effect of oxidative wear in the test under the 8.3-N load in this study could be confirmed by constructing curves of the wear rate under the contact load to illustrate the wear transition that has been described by Cozza [12]. Further tests under different loads should be performed in a future study for this purpose.…”
Section: Wear Tests On the Base Materialssupporting
confidence: 66%
“…The combination of the application of high loads under insufficient lubrication can cause severe adhesive wear on the surface of sliding metallic components. This damage is characterised by the presence of macroscopically visible fragments that adhere onto the two contact surfaces 12 . In our case, metal particles adhered to the respective sphere, which increased the severity of the wear on the material and left a wear track on the sphere.…”
Section: Methodsmentioning
confidence: 99%
“…It also can be seen that for smallest sliding distances, the k values exhibit a random behavior (transient wear regime). As described by Cozza [25], there is no fixed sliding distance for obtaining the steady-state wear, since this depends on the characteristics of the tribological system. Therefore, it is important to consider the effect of samples surface morphology (structure and composition) on the wear regime.…”
Section: Effect Of Abrasive Particle Sizementioning
confidence: 99%
“…Pode-se verificar a existência de muitos dispositivos de micro desgaste por abrasão disponíveis nos principais centros de pesquisa do país [10,11,12,13,14,15,16].…”
unclassified